HUMAN CAPITAL APPROACH TO DEVELOPING FINANCIAL LITERACY IN THE DIGITAL ERA - Eshpulatova Muazzam Barnoyevna (TADQIQOTLAR, 2025)
Abstract The rapid digitalization of financial systems has fundamentally transformed the way individuals interact with financial markets, institutions, and services. While digital financial technologies have increased access to financial products and enhanced financial inclusion, they have also introduced new risks related to information asymmetry, behavioral biases, and digital fraud. This extended thesis examines the development of financial literacy in the digital era through the human capital approach. It argues that financial literacy—particularly digital financial literacy—should be treated as a core component of human capital that directly influences financial behavior, economic security, and sustainable development. Drawing on human capital theory, behavioral economics, and international empirical evidence, the study highlights the importance of education, institutional coordination, and digital competencies in strengthening financial literacy and ensuring responsible financial behavior in the digital age.